KEBIASAAN MEMBERIKAN MAKANAN KEPADA BAYI BARU LAHIR DI PROPINSI JAWA TENGAH DAN JAWA BARAT (NEW BORN INFANT FEEDING HABIT IN CENTRAL JAVA AND WEST JAVA) - Widodo, Yekti (Badan Penelitian dan Pengembangan Kesehatan, 2001)
Initiation of breast milk should be given to the baby as soon as possible, not more than half hour after the baby was bora If initiate of breast milk is not early, it will be difficult to avoid introduced other food than breast milk to new bom be infant. The objective of research is to know how the community habit, especially in Central Java and West Java in order with infant feeding for new born infant The result of the research showed 77,0% respondent introduced other food to new born infant and 23% respondents initiated breast milk soon after the baby bora Two reason for mother introduced other food before they give breast milk First, as